Work Engagement Among Public Employees: Antecedents and Consequences - Khusanova, Rushana; Kang, Seung-Wan; Choi, Suk Bong (Frontiers in Psychology, 2021)
This study is an investigation of the relationships among job meaningfulness, work engagement, and performance, including testing for a possible mediation effect of work engagement on the relationship between job meaningfulness and performance. We examine task interdependence as a boundary condition that facilitates employee engagement using two-stage multiple-source respondent data drawn from a sample of 183 Uzbek employees from public organizations and their 47 supervisors to test the hypotheses. The research findings confirm a positive association between job meaningfulness and engagement and the relationship between work engagement and performance. Mediation analysis using bootstrapping indicated that work engagement explained the influence of meaningfulness on performance. Furthermore, task interdependence negatively moderated the relationship between meaningfulness and engagement. This study responds to calls for researchers to identify the key and situational drivers of work engagement as well as examine the importance of meaningfulness in the public sector. It also increases the external validity of the findings by examining the relationship between engagement and performance in a non-Western context, namely, Islamic Uzbekistan. Despite the limitations of this research, the empirical findings contribute to the growing body of research on work engagement and meaningfulness in public organizations.